HIV incidence, knowledge, attitude and practices of HIV/AIDS and antiretroviral therapy use in HIV-infected patients at Debre Elias district, North West Ethiopia - Melese Birmeka; Damtew Bekele; Megabi Anteneh (PAGEPress Publications, 2024)
Due to hotspots as development schemes that attract mobile groups, HIV/AIDS infections are the biggest health issue in communities with low awareness and safe practice, especially in smaller towns. This study examined HIV/AIDS and Antiretroviral Therapy (ART) use-related knowledge, attitude, and practice in AIDS patients. Debre Elias Health Center conducted a cross-sectional study (N=384) from June 10 to January 20, 2021. Participants were selected using systematic random sampling and interviewed using a structured questionnaire. Logistic regression calculated significance and association between dependent and independent variables. 236 (384) or 61.4% of 384 HIV patients on antiretroviral therapy were female. HIV rates increased from 2014 to 2019. Age difference was associated with patient knowledge of ART use (P=0.005). Patients' attitudes towards HIV/AIDS and ART use were significantly correlated with age, residence, marital status, and education (P<0.001). HIV patients 25-30 were 2.2 times more likely to know about ART use. HIV patients with a degree or higher were five times more likely to support ART. HIV patients aged 14-24 with a positive ART outlook were 94% protective. HIV prevalence is rising, especially among 15 to 24-year-old women. Public protection is needed to reduce HIV transmission.